USAGES TRADITIONNELS DE QUELQUES ESPECES VEGETALES DE LA FORET MARECAGEUSE CLASSEE DE PORT GAUTHIER, EN ZONE COTIERE AU SUD-OUEST DE LA COTE D’IVOIRE - Sibirina, Soro; Djakalia, Ouattara; Mathieu, Egnankou Wadja; Edouard, N’guessan Kouakou; Dossahoua, Traore (European Scientific Journal, ESJ, 2014)
Swamp forest classified Port Gautier is an edaphic freshwater formation that developed in poorly drained permanent waterlogging in the coastal zone Fresco lowlands in southwest of Côte d’Ivoire. Despite its protected status and its difficult access, vegetation and flora of the forest is highly degraded by the local populations. This is in order to determine the reasons for the illegal logging that ethnobotanical study was conducted with the participation of local populations. The study has identified 20 plant species belonging to multiple traditional uses 16 genera and 10 families collected in the swamp forest. Organs and harvested plants are used in the fields of the pharmacopoeia (11 species), food (7 species), crafts (5 species), the construction of the boxes (5 species) and other areas (8 species). Although permanent all year, organ harvesting and plants are most important during the two dry seasons.